2015
DOI: 10.1063/1.4916348
|View full text |Cite
|
Sign up to set email alerts
|

Formation of BaSi2 heterojunction solar cells using transparent MoOx hole transport layers

Abstract: Heterojunction solar cells that consist of 15 nm thick molybdenum trioxide (MoOx, x < 3) as a hole transport layer and 600 nm thick unpassivated or passivated n-BaSi2 layers were demonstrated. Rectifying current-voltage characteristics were observed when the surface of BaSi2 was exposed to air. When the exposure time was decreased to 1 min, an open circuit voltage of 200 mV and a short circuit current density of 0.5 mA/cm2 were obtained under AM1.5 illumination. The photocurrent density under a reverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…19 According to Ref. 19, the capacitance versus voltage characteristics of the device structures composed of the native oxide/BaSi 2 interface revealed that the trapped electrons at the surface defect states decreased with the air exposure duration of the BaSi 2 surface. On the basis of these results, the band lineup of the native oxide layer and BaSi 2 can be obtained as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 According to Ref. 19, the capacitance versus voltage characteristics of the device structures composed of the native oxide/BaSi 2 interface revealed that the trapped electrons at the surface defect states decreased with the air exposure duration of the BaSi 2 surface. On the basis of these results, the band lineup of the native oxide layer and BaSi 2 can be obtained as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we have recently achieved the solar cell operation in the devices utilizing the native oxide/n-BaSi 2 heterointerface. 19 The efficiency was quite limited because the transport of photogenerated minority carriers (holes) was blocked by the native oxide. In order to improve the device performance, extraction of the photogenerated holes more efficiently through the native oxide layer via tunneling is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in this study, we first aimed to lower the temperature of the B Knudsen cell crucible, T B , from that in our previous studies to reduce N B and then investigated the dependence of the activation rate on T B to find an appropriate T B . We next adopted the optimum T B and fabricated p-BaSi 2 (20 nm)/n-Si heterojunction solar cells by MBE, whereby g reached 9.0%, which is approximately 100 times larger than those ever reported for BaSi 2 solar cells 24,32 and is much higher than any other solar cell consisting of semiconducting silicides. 33,34 An ion-pumped MBE system equipped with an electronbeam evaporation source for Si as well as standard Knudsen cells for Ba and B was used in this investigation.…”
mentioning
confidence: 98%
“…It is also consistent with a recent first-principles calculation using the Heyd-Scuseria-Ernzerhof screened hybrid functional 21 and photon energies obtained from photoresponse measurements, above which the photoresponsivity of BaSi 2 begins to increase, regardless of the BaSi 2 layer thickness. [22][23][24] One of the most striking features of this material is that both a large a and large minority-carrier diffusion length, L, can be utilized. This facilitates the collection of photogenerated carriers in an external circuit.…”
mentioning
confidence: 99%
See 1 more Smart Citation